Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Berbasis Web Pada Rumah Sakit Paru Surabaya - Mindrawan, Tantri; Setyawan, Henry Bambang; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Employee performance evaluation in Paru Surabaya Hospital consists of two ratings. Those are employee performance appraisal and assessment of employee performance at the working unit. Human Resources (HR) find miscalculation cases on those assessments due to miscalculation of the applied assessment formula. This miscalculation mostly occurred on three to five employees each year. Another problem that also occurs on managerial level is the evaluation report establishment takes one to two weeks in average due to must open the recapitulation file of employee performance evaluation. The applied solution to overcome these problems is developing the application of employee performance appraisal using Key Performance Indicator by looking at four aspects: quantity, quality, time and cost. While the employee performance evaluation at the departement using Graphic Rating Scale method. Based on trial results between manual calculation and application is made to the nine employees who represent their respective departments, the result that there is no difference between manual calculations with the application so that the application can perform calculations accurately. The trial results show a report with twenty employees value the data takes approximately thirty seconds so as to display the entire data value employee report 216 employees take approximately five minutes.